Growth and development of syphilis-exposed and -unexposed uninfected children during their first 18 months of life in Suzhou, China: a nested case–control study with propensity score matching - Gong, Tian; Zhong, Yi; Ding, Yaling; Wu, Qianlan; Yao, Mengxin; Yin, Jieyun; Shao, Yan; Liu, Juning (Frontiers in Public Health, 2023)
Background: With the successful implementation of Prevention of Mother-to-Child Transmission (PMTCT) policies, the proportion of infants with exposure to both syphilis and antibiotic medication in utero has increased in China, but there is limited evidence about the early growth and development of such infants.We conducted a retrospective nested case-control study based on data from the China PMTCT program conducted in Suzhou from 2016 to 2021. Propensity score matching (PSM) was employed to extract 826 syphilis-exposed but uninfected (SEU) infants and 1,652 syphilis-unexposed uninfected (SUU) infants from a total of 712,653 infants. Maternal characteristics were collected through questionnaires, such as parity, age, education level, smoking and drinking habits during pregnancy. Infantile characteristics were retrieved from medical records or via questionnaires, such as gestational age, gender, mode of delivery, Apgar scores, birth weight and length, outdoor time, vitamin D intake, and feed pattern. Mixed effects models, adjusting for potential influencing factors, Syphilis Exposure and Growth Curves 2 were used to investigate the early infantile growth pattern of SEU and SUU infants. All statistical analysis were conducted using R (version 4.2.0).Results: Length and weight were slightly higher in SEU infants than in the SUU infants at some time points (months 0 and 18 for length, P values < 0.05; months 0, 6, and 18 for weight, P values< 0.05).In the mixed effects model, SEU group was found to be associated with higher weight (exponentiated beta exp(β) = 1.15, 95% Confidence Interval (CI) = 1.06, 1.25), length (exp(β) = 1.42, 95% CI = 1.14, 1.77), and BMI z-score (exp(β) = 1.09, 95% CI = 1.00, 1.19).With the effective prevention of congenital syphilis under the PMTCT program, SEU infants have non-inferior growth patterns during their first 18 months of life compared with SUU controls in Suzhou, China.